EFFECT OF MALEIC ANHYDRIDE POLYPROPYLENE ON THE PROPERTIES OF COCONUT SHELL FILLED THERMOPLASTIC ELASTOMERIC OLEFIN COMPOSITES - Z.H. Tengku Faisal; Faisal Amri; Iqmal Tahir (Universitas Gadjah Mada, 2010)
Coconut shell (CS) is one of agro-waste material which has high natural lignocellulosics content. This material provides a potential resource as a reinforcement agent in thermoplastic elastomeric olefin (TEO). In this study, CS was used as filler in TEO composites. The effect of CS loading and Maleic Anhydride Polypropylene (MAPP) as compatibilizer on mechanical properties, morphology and thermal properties were studied. Results show that the increasing of CS loading has increased the tensile strength, elongation at break and Young's modulus of TEO/CS composites. At similar content, the effect of PP-g-MA as compatibilizer has improved the tensile strength, elongation at break and Young's modulus of TEO/CS composites. The SEM study of the tensile fracture surface of compatibilized composites indicates that the presence of PP-g-MA increased the interfacial interaction. TGA results show that the composites with addition of MAPP as a compatibilizer has better the thermal stability compared to composites without addition of MAPP at 600 °C. DSC analysis showed that the addition of MAPP decreases the crystallinity of TEO/CS composites. It was found that the presence of MAPP will extended the molecular chain of the TEO/CS composites.